Pansacramentalism, Interreligious Theology, and Lived Religion - Gustafson, Hans (Religions, 2019)
Opening with a philosophical definition of sacrament(ality) as a mediator (mediation) of the sacred in the concrete world, this article offers pansacramentalism as a promising worldview-especially for those rooted in or emerging from the Christian traditions (since, for them, the language of sacramentality may have a stronger resonance)-for bringing together interreligious theology and data mined by Lived Religion approaches to the study of religion. After articulating the concept of pansacramentalism and emphasizing interreligious theology as an emerging model for doing theology, growing trends and changing sensibilities among young people's religious and spiritual lives (e.g., the "Nones") is considered insofar as such trends remain relevant for making contemporary theology accessible to the next generation. The article then considers the intersection of pansacramentalism and interreligious theology, especially the issue of determining sacramental authenticity. To explain how this challenge might be met, Abraham Heschel's theology of theomorphism is offered as but one example as a nuanced means for determining sacramental authenticity of the sacred in the world. Turning to "Lived Religion" approaches, rationale is offered for why pansacramentalism and interreligious theology ought to be taken seriously in the contemporary world, especially considering recent data about the nature of contemporary religious identities among young people living in the West.